Implementation of the primary health care system in various countries: a systematic review - Setya Budi, Rocky; Adisasmito, Wiku Bakti Bawono (Universitas Gadjah Mada, 2023)
Purpose: Primary health care (PHC) focuses on the community as individuals, families, and communities, which prioritizes health promotion and disease prevention over treatment, rehabilitation, and palliative care. PHC implementation often sacrificed the prevention approach because it was hampered by health medicalization. Methods: This Systematic Review follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The author searched five databases: EMBASE, ProQuest, ScienceDirect, Scopus, and PubMed, to discover the primary health care system implementation in various countries. Result: Searches on the EMBASE database included 193 articles, ProQuest 347 articles, PubMed 589 articles, ScienceDirect 294 articles, and Scopus 293 articles. Reports were assessed for eligibility, the remaining 39 full-text articles were reviewed, and the authors chose ten relevant and suitable articles for further review. Conclusions: The medicalization of health, a shortage of skilled health workers, poor services, a weak referral system, treatment that does not meet the needs of the community, a lack of public-private partnerships in the provision of health services, and a lack of stakeholder involvement in policy-making continues to impede PHC implementation. In the future, stakeholders should cover the gap between public health and primary care through integration.